Do Innovation in Environmental-Related Technologies and Renewable Energies Mitigate the Transport-Based CO2 Emissions in Turkey? - Alnour, Mohammed (Frontiers in Environmental Science, 2022)
Given the unprecedented level of air pollution in urban areas, green transport systems has been a subject to an important debate in academic and policymaking circles. Despite the considerable outputs of the attendant literature, most of empirical studies to date have relied on conventional econometric models in which structural shocks are not controlled. This study, therefore, aims to offer a new perceptive of the dynamic connection between renewable energy, environment-related technological innovation, and transport-based CO2 emissions in Turkey during 1990Q1 to 2014Q1 by applying the Structural Vector Autoregressive approach (SVAR). Furthermore, to explore the co-movements and the lead-lag interrelations among the study variables, the wavelet coherence technique was used. The wavelet coherence technique circumvents the other traditional causality approaches by detecting the causal interrelation between the underlying series at different frequencies. The findings disclose that environment-related technological innovation has no reliable power to explain the variation in CO2 emissions from the transport sector. Solar energy is found to impact the CO2 emissions positively in the long run, while biofuels hold the same effect in short run. Moreover, per capita GDP and urbanization significantly impact the carbon emissions from the transport system in the long run with a negative sign. The wavelet analysis reveals that renewables and environmental-related technological innovation lead the transport-based CO2 emissions. The fourth and 16th periods are the most dominant frequencies. Accordingly, the study suggests that innovation in environment-related technologies is not enough to mitigate the pollution that stemming from the transport system in Turkey, it should be accompanied by strong and effective environmental measures. These policies might include environmental taxations, carbon pricing and trading schemes, which aim not only to prevent the pollution and over-extraction of resources, but also to promote the public revenues from different activities that related to environmental purposes and other applications such as energy product and vehicle fuels. In addition, it is suggested to strengthening the transportation system through the deployment of renewables and high-tech eco-friendly modes of transportation.